A Critical Discourse Analysis on the Representation of Rape among Sudanese Women on Al-Jazeera.Net - Aprilia, Lulu Eka; Al Anshory, Abdul Muntaqim (Balai Bahasa Kalimantan Tengah, 2024)
Global media attention has focused on the protracted conflict between the Sudan Armed Forces and the Rapid Support Forces in the Sudanese region. This war has led to an alarming increase in violations of women's rights, particularly cases of violence against women. This research aims to examine and reveal the positions of subjects and objects, as well as the portrayal of rape perpetrators in Al Jazeera news. The research method employed is qualitative descriptive analysis. Data sources are derived from the Al Jazeera portal broadcasted on August 16, 2023, with the page titled